Characterisation and genome analysis of novel quorum sensing soil bacteria / Robson Ee Han Jen - Robson Ee , Han Jen (2016)
Quorum sensing (QS) describes bacterial communication using signalling molecules. QS is important for regulation of various gene expressions, most notably for the survival and adaptation of a population of bacteria to the surrounding environment. The objective of this study was to isolate and characterise novel QS bacteria. Preliminary screening of QS activity was performed using both Chromobacterium violeceum CVO26 and Escherichia coli [pSB401] biosensors. Isolates exhibiting QS activity were subsequently identified using polyphasic identification methods and their QS profile was eventually characterised using mass spectrometry. Out of 60 isolates, only two novel QS isolates were selected for further investigation. The first novel QS bacterium was Chania multitudinisentens RB-25T which was a newly proposed genus in the family of Enterobacteriaceae. This isolate was found to produce 3 AHLs: C4-HSL, C6-HSL and 3-oxo-C6-HSL. Various taxonomical analyses (for example phenotypic and genotypic characterization) according to Bergey’s Manual of Systematic Bacteriology had been conducted to characterise this isolate. The complete genome sequences unveiled presence of two pairs of luxI/R in C. multitudinisentens RB-25T and gene cloning performed validated the AHL synthesis activities of these AHL synthases. This discovery added C. multitudinisentens RB-25T to the increasing documentation of QS members in the phylum of Proteobacteria. The second novel QS bacterium isolated was strain RB-38 which was later identified as Pandoraea pnomenusa. Mass spectrometry analysis revealed that C8-HSL was the only signaling molecules detected from the spent supernatant of P. pnomenusa RB38. As this was the first documentation of QS activity in Pandoraea genus, we sequenced the complete genome of P. pnomenusa RB-38 to study its QS synthase. A set of luxI/R (designated as ppnI/R1) and an orphan ppnR2 were identified from the genome in which functional studies of PpnI conducted confirmed its role in the production of C8-HSL.